KEANEKARAGAMAN SERANGGA TANAH DI TAMAN WISATA ALAM (TWA) BATUPUTIH - Nita Patale; Terry M. Frans; Marthen Th. Lasut Marthen Th. Lasut (COCOS, 2022)
Abstract Soil insects are a type of insects that inhabit litter or soil. In almost of their lives the abundance and dominance of insects in a ecosystem is influenced by litter on the forest superficies. The purpose of this research is to determine the diversity of soil insects in coastal forest and lowland forest ecosystem types in Batuputih Nature Park (Taman Wisata Alam Batuputih). This research used Purposive Sampling method at two different locations: Coastal forest and lowland forest. The sampling technique that used in this research is trap. Based on the result of research conducted in Taman Wisata Alam (TWA) Batuputih, there are 7 species of soil insects found in the coastal forest ecosystem type, 12 species in the lowland forest ecosystem type, and 2306 individual soil insects from 11 families contained in these ecosystems. The spesies diversity index in Taman Wisata Alam (TWA) Batuputih is low with the spesies diversity index in coastal forest (H’=1.126), lowland forest (H’=1.219) and both of those ecosystems (H’=1.257). The spesies abundance and soil insects spesies diversity index in lowland forest ecosystem types are higher than coastal forest ecosystem types. Key Words: Soil Insect, Diversity, Taman Wisata Alam Batuputih